Do they do it for the money? - Bhattacharya, Utpal; Marshall, Cassandra D. (Journal of Corporate Finance, 2012)
Using a sample of all top management who were indicted for illegal insider trading in the United States for trades during the period 1989–2002, we explore the economic rationality of this white-collar crime. If this crime is an economically rational activity in the sense of Becker (1968), where a crime is committed if its expected benefits exceed its expected costs, “poorer” top management should be doing the most illegal insider trading. This is because the “poor” have less to lose (present value of foregone future compensation if caught is lower for them). We find in the data, however, that indictments are concentrated in the “richer” strata after we control for firm size, industry, firm growth opportunities, executive age, the opportunity to commit illegal insider trading, and the possibility that regulators target the “richer” strata. We thus rule out the economic motive for this white-collar crime, and leave open the possibility of other motives.